The Navajos - Sneve, Virginia Driving Hawk (Sneve, Virginia Driving Hawk. First Americans book., 2025)
In this new and updated edition, award-winning author Virginia Driving Hawk Sneve introduces young readers to the Navajo, or Diné, peoples. Did you know that Navajo children were given their own lambs to signal their transition into adulthood? Learn about the Navajo's creation story, resistance and resilience against Spanish colonizers, forked-stick hogan homes, sand paintings, and more. Expertly reviewed by a member of the Navajo tribe, this updated edition provides the most up to date and accurate information on the Navajo people of the past and present. Historical information is accompanied by a section on modern life and contemporary photos Author Virginia Driving Hawk Sneve grew up on the Rosebud Sioux Reservation and is an enrolled member of the Rosebud Sioux tribe. She has brought the richness of Native American culture and heritage to thousands of children for over 40 years as a teacher and children's book author. Her First Americans books introduce young readers to the many diverse and unique Native American nations that first called this land home.